Directive Pedagogical Management and Productive Educational Projects in the educational institutions of the district of Azángaro Province of Yauyos - Lima, 2020 - Flores Alfaro, Edith Kredis (2021)
The objective of the research is to determine the relationship between the directive pedagogical management and the Productive Educational Projects in the Educational Institutions of the district of Azángaro province of Yauyos - Lima, 2020. For its development, the correlational  research was considered in which the link will be analyzed statistical between two variables, applying a questionnaire for each variable applied to a sample of 88 teachers, whose data collected were processed through the statistical program SPSS, in addition, Spearman's Rho was used with a margin of error of 5%. The results found a correlation level of 0,904 showing a relationship between directive pedagogical management and productive educational projects, due to the majority results of directive pedagogical management considered indifferent by 73.9%, which is linked to productive educational projects seen by the 71.6% with a frequency of sometimes. In the same way, the relationship of the first variable with the relevance, objectivity, commitment and creativity dimensions was confirmed. Therefore, it was concluded that an intermediate management of the directors within the institution limits the institutional interest (teachers, students and parents), for the effective development of educational projects.